Year Six pupils thrilled to join UMP students for iftar in campus - UMP, PNC (2019)
It was an exciting experience for 41 Year Six pupils from Sekolah Kebangsaan Serandu in Pekan for they got to join their facilitators and Universiti Malaysia Pahang (UMP) students for iftar in the university’s campus in Pekan on May 14, 2019.